PENGEMBANGAN PARIWISATA SPIRITUAL BERBASIS TEOLOGI HINDU BAGI UMAT HINDU DI KAWASAN PULAKI KABUPATEN BULELENG - Ida Ayu Dwidyaniti Wira (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
Gerogak District, Buleleng Regency with several temples scattered along the coastline, making it a good place or destination for spiritual tourism. Spiritual tourism is the oldest type of tourism. Spiritual tourism began to be developed by the Buleleng Regency government. Gerogak District has also begun to develop spiritual tourism. The purpose of this study was to explore the readiness of Gerogak District, especially comrades Pulaki, as a spiritual tourism destination. Data were collected from Hindu tour guides. This research shows that Pulaki Temple, and several surrounding temples with spiritual activities can be developed as spiritual tourism destinations. Based on the existence of these temples, tour guides are asked to identify the readiness of these temples as spiritual tourism destinations. The results show that the Pulaki area in Gerogak District is ready to become a spiritual tourism destination because of the existence of temples around it. The temples are equipped with a community hall as a place to meet or discuss spiritual matters. The community hall is also a place to meditate, rest or spend the night.